No-tillage, green manure and supplementation with poltry manure on organic eggplant production - Castro, Cristina Maria de; Almeida, Dejair Lopes de; Ribeiro, Raul de Lucena Duarte; Carvalho, Jaqueline Fernandes de (Pesquisa Agropecuaria Brasileira, 2005)
No-tillage systems were evaluated within an eggplant (Solanum melongena) organic management in Seropédica, Rio de Janeiro State. Crotalaria juncea and Pennisetum glaucum cv. BRS 1501 were used as pre-plantings besides fallowing, in comparison to conventional system (plowing). Simultaneously, three cropping managements were tested: eggplant single-cropping, intercropping with C. juncea, and intercropping with cowpea (Vigna unguiculata cv. Mauá). No differences were found among planting systems concerning eggplant yield. Crotalaria juncea was more effective than Pennisetum glaucum and fallow for soil mulch. Intercropping with leguminous species did not decrease eggplant yield. In a second study no-tillage (on C. juncea and spontaneous weeds mulchs) and conventional plowing were compared. These treatments were combined with increasing levels of poultry manure (0, 100, 200, and 400 kg ha-1 of N). In terms of biomass input, C. juncea was again superior to spontaneous weeds. Eggplant responded to organic fertilization with maximum productivity (50.6 t ha-1) corresponding to the highest manure level applied, compared to 36.9 t ha-1 for control plots.